Annotated index of Tula Dula scripts from 1977-2017 - Coloma, Wynonah Charise I.; Cabbab, Johann Frederick A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2019)
Tula Dula are short stage plays that were written by scriptwriters to pepict the story and life cycle/struggles most Iskolar ng Bayan faced. This paper aims to zero in on which themes were prevalently used by scriptwriters.

Three themes most frequently used were: 1. Students/Iskolar ng Bayan/Working Students ; 2. Tuition Fee/Hike/STFAP ; 3. Gobyerno/Makapangyarihan.

“Dorm”, “Probinsya”, “Sakit”, and “Gamot” were amongst the themes least used as main themes but were used as sub-themes to the top three themes.
Thesis (Bachelor of Library and Information Science)
Keywords: UP Repertory Company; Philippine poetry -- Indexes; Philippine drama -- Indexes